2009
DOI: 10.4319/lom.2009.7.371
|View full text |Cite
|
Sign up to set email alerts
|

Determination of ultra‐low oxygen concentrations in oxygen minimum zones by the STOX sensor

Abstract: The methods used until now have not been able to reliably resolve O 2 concentrations in oceanic oxygen minimum zones below 1-2 µmol L -1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
275
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(284 citation statements)
references
References 20 publications
8
275
1
Order By: Relevance
“…Dissolved oxygen concentration, as measured by the CTD oxygen sensor, decreased from fully saturated at the surface to o2.5 mM (that is, at the detection limit of the CTD oxygen sensor real oxygen concentrations are likely to be substantially lower; see Revsbech et al, 2009;Stolper et al, 2010) within the core of the OMZ and increased again with depth starting at 1050 m (Figure 1b). Sulfide was not detected, indicating the absence of euxinic conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dissolved oxygen concentration, as measured by the CTD oxygen sensor, decreased from fully saturated at the surface to o2.5 mM (that is, at the detection limit of the CTD oxygen sensor real oxygen concentrations are likely to be substantially lower; see Revsbech et al, 2009;Stolper et al, 2010) within the core of the OMZ and increased again with depth starting at 1050 m (Figure 1b). Sulfide was not detected, indicating the absence of euxinic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The copy numbers of archaeal 16S rDNA were estimated by using the 16S rDNA specific primers Parch519F and ARC915R (Coolen et al, 2004); Thaumarchaeota (MCG1) 16S rDNA with MCGI-391F and MCGI-554R primers as described by Coolen et al (2007); archaeal amoA with primers CrenAmoAQ-F and CrenAmoAModR (Mincer et al, 2007); and 16S rDNA anammox with Brod541F and Amx820R as described by Li et al (2010). For the quantification of the hzo gene, hzo primers hzo_LV2F and (Revsbech et al, 2009). Persian Gulf Water (PGW) and to a much lesser extent, Red Sea Water (RSW), influence the OMZ at our study site.…”
Section: Q-pcr Analysismentioning
confidence: 99%
“…The standard oxygen sensor of the conductivity-temperature-depth (Seabird) and an additionally mounted microsensor were used together to identify the OMZ. Besides, we deployed the highly sensitive STOX (Switchable Trace amount OXygen) sensor (Revsbech et al, 2009;detection (Figure 1). NH 4 þ and NO 2 À concentrations were measured immediately after sampling using fluorometric and spectrophotometric techniques, respectively (Grasshoff, 1983;Holmes et al, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…However, we have no indication that Methylobacter possesses this trait, and nitrite was not detectable in another microcosm experiment with the same soil . Recently developed microelectrodes (Revsbech et al, 2009;Revsbech et al, 2011) have demonstrated nanomolar oxygen concentrations in areas that have been considered anoxic so far. However, the design of our microcosms includes a trap to remove any oxygen that might have diffused into the lower compartment (Murase and Frenzel, 2007).…”
Section: High-resolution Spatial Analysis Of Methanotrophs a Reim Et Almentioning
confidence: 99%